FORMULATION OF THE NEW BUSINESS MODEL CANVAS BCA KIMA BRANCH WITH INTEGRATING THE DYNAMIC CAPABILITY STRATEGY TO ACHIEVE OPTIMAL PERFORMANCE - Junalt Imanuel Machelt (Scientia Integritas Utama, 2023)
In today's competitive banking industry, BCA Branch Banking needs to formulate a competitive strategy to achieve optimal performance. This study aims to describe the current business strategy of the BCA Industrial Estate branch, and examine the dynamic capabilities possessed by the branch whether it is able to identify strengths, weaknesses, opportunities and threats that exist. This research is a type of strategic design research based on scientific analysis and argumentation. Data collection uses primary data and secondary data. In terms of methods or techniques of data collection, data collection techniques are carried out by observation, interviews through key informants and documentation. Primary and secondary data analysis used a qualitative approach to Business Model Canvas, dynamic capability analysis and SWOT analysis. The results of this study indicate that the branch's current business strategy needs to be reformulated into a New Business Model Canvas. Then from the results of the dynamic capability analysis it shows that the branch has not been able to optimize its dynamic capabilities to identify existing strengths, weaknesses, opportunities and threats so that BCA Kima Branch needs to carry out improvement strategy to be able to identify market opportunities, capture existing opportunities, and combine and reconfigure existing assets to achieve optimal performance.